Blue light-dependent interactions of CRY1 with GID1 and DELLA proteins regulate gibberellin signaling and photomorphogenesis in Arabidopsis. Issue 7 (6th May 2021) - Xu, Peng; Chen, Huiru; Li, Ting; Xu, Feng; Mao, Zhilei; Cao, Xiaoli; Miao, Langxi; Du, Shasha; Hua, Jie; Zhao, Jiachen; Guo, Tongtong; Kou, Shuang; et al.
Abstract: Cryptochromes are blue light photoreceptors that mediate various light responses in plants and mammals. In Arabidopsis ( Arabidopsis thaliana ), cryptochrome 1 (CRY1) mediates blue light-induced photomorphogenesis, which is characterized by reduced hypocotyl elongation and enhanced anthocyanin production, whereas gibberellin (GA) signaling mediated by the GA receptor GA-INSENSITIVE DWARF1 (GID1) and DELLA proteins promotes hypocotyl elongation and inhibits anthocyanin accumulation. Whether CRY1 control of photomorphogenesis involves regulation of GA signaling is largely unknown. Here, we show that CRY1 signaling involves the inhibition of GA signaling through repression of GA-induced degradation of DELLA proteins. CRY1 physically interacts with DELLA proteins in a blue light-dependent manner, leading to their dissociation from SLEEPY1 (SLY1) and the inhibition of their ubiquitination. Moreover, CRY1 interacts directly with GID1 in a blue light-dependent but GA-independent manner, leading to the inhibition of the interaction between GID1 with DELLA proteins. These findings suggest that CRY1 controls photomorphogenesis through inhibition of GA-induced degradation of DELLA proteins and GA signaling, which is mediated by CRY1 inhibition of the interactions of DELLA proteins with GID1 and SCF SLY1, respectively. Abstract : Blue light-dependent interactions of CRY1 with GID1 and DELLA proteins inhibit gibberellin (GA)-induced degradation of DELLA proteins to regulate GA signaling and photomorphogenesis.